FATIGUE FRACTURE ANALYSIS OF EXCAVATOR BOOM BASED ON FULL-SCALE ACCELERATED LOADING TEST (MT) - XIANG QingYi; Lü PengMin; WANG PengHui (Jixie qiangdu)
To analyze the fatigue fracture causes of boom during normally working service, the boom bench fatigue test scheme was proposed. The measured joints multi-load was equivalent to a uniaxial load based on the fatigue damage consistent principle. Moreover, the calculated fatigue damage caused by the equivalent uniaxial load is in the same order of magnitude as the measured damage of each boom fatigue key point, and the relative error is within 8%. The full-scale accelerated loading fatigue test of four large and medium-sized excavator′s boom was carried out under the accelerated 5-level program loading spectrum compiled from the equivalent uniaxial load. The fatigue fracture surface was analyzed by scanning electron microscope. The results show that the boom fatigue life is relatively discrete, and the fatigue crack originates from the stress concentration point caused by welding defects such as incomplete penetration, incomplete fusion and gas porosity. After targeted improvements to the weld structural details of a boom based on bench test results, its fatigue life is increased by at least 1.5 times. The predicted life of commonly used international welding standards, BS7608-2015, IIW2008 and AWS-2015, is relatively close to the bench fatigue test results of the 2nd and the 3th boom, while the predicted life of standard EN-2005 is longer. With the bench fatigue test, the fatigue strength weak parts of booms and other similar structures can be effectively inspected, which provides a valuable reference for structural improvement.